EFFECT SCIENTIFIC INQUIRY TEACHING MODELS AND SCIENTIFIC ATTITUDE TO PHYSICS STUDENT OUTCOMES - Dian Clara Natalia Sihotang (Jurnal Pendidikan Fisika, 2014)
The objectives of this study were to determine whether: (1) the student’s achievement taught by using Scientific Inquiry Teaching Models is better than that of taught by using Direct Instruction; (2) the student’s achievement who have a high scientific attitude is better than student who have low scientific attitude; and (3) there is interaction between Scientific Inquiry Teaching Models and scientific attitude for the student’s achievement. The results of research are: (1) the student’s achievement given learning through Scientific Inquiry Teaching Models better than Direct Instruction; (2) the student’s achievement who have a high scientific attitude better than student who have low scientific attitude; and (3) there was interaction between Scientific Inquiry Teaching Models and scientific attitude for student’s achievement which this models is better to apply for student who have a high scientific attitude.